Calorie provision from citrate anticoagulation in continuous renal replacement therapy in critical care. (August 2021) - Rogers, Alice R; Jenkins, Bethan
Background: Citrate is used as a regional anticoagulant for continuous veno-venous haemofiltration and provides 0.59 kcal/mmol. Previous studies hypothesised continuous veno-venous haemofiltration can provide 200–1300 kcal/day dependent on the anticoagulant and replacement solutions used. The aim of this study was to calculate the calorie load from citrate in our patient group. Methods: An equation derived from a paper by Oudemans-van Straaten was used to estimate calorie provision from citrate. Citrate calorie load was defined as the difference between the citrate in the filter circuit and the removal by continuous veno-venous haemofiltration. Clinical data were recorded on 20 consecutive patients admitted to intensive care unit and commenced on citrate continuous veno-venous haemofiltration using prismacitrate 18/0 by Gambro, a tri-sodium citrate solution. Clinical data recorded included patient demographics, filter settings including blood flow, filtration factor, citrate dose and time on filtration daily. Results: A total of 20 critically ill patients received continuous veno-venous haemofiltration for treatment of a new acute kidney injury, mean age 66 years, 65% male. Mean duration of continuous veno-venous haemofiltration was 3.7 days. Mean daily time on filtration was 20 h/day. Mean filtration fraction, citrate dose and blood flow were 30%, 3 mmol/L and 123 ml/min, respectively. Our calculation showed that a mean of 9.5 ± 1.7 cal/h were provided from citrate with a mean daily calorie load of 196 ± 69 kcal. Conclusions: Continuous veno-venous haemofiltration with tri-sodium citrate provided an additional 196 ± 69 kcal/day. The calorie load from citrate continuous veno-venous haemofiltration should be calculated regularly as changes in filter settings, in particular citrate dose and blood flow can have a significant impact on calorie provision.